A two-week regimen of high-dose integrase inhibitors does not cause nephrotoxicity in mice. Issue 2 (April 2015) - Eadon, Michael T; Zhang, Hongji; Skaar, Todd C; Hato, Takashi; Dagher, Pierre C; Gupta, Samir K; Desta, Zeruesenay
Background: The integrase inhibitors, raltegravir and dolutegravir, are nucleoside reverse transcriptase inhibitor-sparing agents which may be used as part of first-line antiretroviral therapy for HIV. These drugs inhibit creatinine secretion through organic cation transporters, thus elevating serum creatinine without affecting glomerular filtration. We sought to determine whether subtle signs of nephrotoxicity could be observed in mice administered a two-week regimen of high-dose integrase inhibitors. Methods: C57BL/6 mice were fed standard water (CTRL, n = 6), raltegravir-containing water (40 mg/kg/day, n = 6), or dolutegravir-containing water (2.7 mg/kg/day, n = 6) for two weeks and sacrificed. Endpoints were assessed including urine microalbumin, kidney injury molecule-1 renal tissue gene expression, renal histopathology, serum creatinine, and blood urea nitrogen. Results: The results are NOT consistent with a direct nephrotoxic effect of the integrase inhibitors in mice. Serum creatinine was significantly elevated in raltegravir and dolutegravir mice (p < 0.05) compared to control (raltegravir = 0.25 mg/dl, dolutegravir = 0.30 mg/dl versus CTRL = 0.17 mg/dl). Blood urea nitrogen, cystatin C, and urine microalbumin were unchanged. Kidney injury molecule-1 tissue expression in raltegravir and dolutegravir groups was nonsignificantly elevated compared to control (1.2-fold compared to control). Renal histopathology by periodic acid–Schiff staining failed to reveal glomerular or tubular renal injury in any group. Conclusion: These studies are consistent with integrase inhibitors competitively inhibiting creatinine secretion. While no evidence of direct nephrotoxicity was observed after two weeks of high-dose drug administration, additional studies may be performed to understand whether these drugs lead to chronic nephropathy.